RELIABILITY ANALYSIS OF TRACKED VEHICLE PLANETARY TRANSMISSION MECHANISM BASED ON FAULT TREE AND BAYESIAN NETWORK - CHEN JiaHui; MI Jie; ZHANG ShengLun; CHEN FuJun (Jixie qiangdu)
Planetary transmission mechanism is the core part of tracked vehicle transmission system, its reliability directly affects the tracked vehicle normal operation. Taking tracked vehicle planetary transmission mechanism as the research object, the fault tree was established based on the measured test results, and the fault tree was transformed into a Bayesian network (BN) model, and the reliability analysis was carried out considering the planetary transmission mechanism three states of normal general failure and serious failure . The results show that planetary transmission mechanism failure probability is 89.34×10-8 h-1.and its reliability is 0.999 64 for 400 hours, which meets the design requirements. Using Bayesian network bidirectional calculation function, planetary transmission mechanism fault is more likely to be caused by the main shaft fracture or friction plate ablation, warping, fracture or gear fatigue broken teeth. It provides a theoretical basis for subsequent equipment maintenance and improvement design.